Financing Sources For Education Investment In Islamic Boarding Schools In North Sumatra: A Case Study Of Salafiyah Raudatul 'Ulum And Modern Al-Abraar Islamic Boarding Schools - Abdi, Usman; Mesiono, Mesiono; Budianti, Yusnaili (Edukasi Islami: Jurnal Pendidikan Islam, 2023)
This study aims to analyze the financing of educational investments in two types of Islamic boarding schools, namely Pondok Pesantren Salafiyah Raudatul 'Ulum in Aek Nabara, Labuhan Batu, North Sumatra, and Pondok Pesantren Modern Al-Abraar in South Tapanuli, North Sumatra. The study employs a multisite approach to understand various aspects influencing educational financing in these boarding schools. The research reveals that both boarding schools have different financing models but share the common goal of enhancing educational quality. Pondok Pesantren Salafiyah Raudatul 'Ulum relies on endowment funds (wakaf), community donations, and contributions from students and alumni. In contrast, Pondok Pesantren Modern Al-Abraar combines funds from various sources such as regular donors, scholarships, and income from productive economic activities managed by the boarding school. Findings indicate that despite having different financing strategies, both boarding schools face similar challenges in managing funds and ensuring the sustainability of quality education. The study suggests the need for diversifying funding sources and adopting more professional financial management to enhance the effectiveness of educational financing in boarding schools. This research makes a significant contribution to the literature on educational financing in Islamic boarding schools and serves as a reference for other boarding school administrators in developing effective and sustainable financing strategies.